Accessory Extraocular Muscle: A Rare Cause of Strabismus - Ana Carolina Chaves; Catarina Paiva; Sílvia Carvalho (Journal of the Belgian Society of Radiology)
Teaching point: Accessory extraocular muscles are rare intraorbital congenital structures that can cause diplopia and restrictive strabismus.